German Elementary Education from 1890 To 1945 Lessons about Religion, Home, and Fatherland - Kennedy, Katharine (Oxford De Gruyter, 2025)
List of FiguresAcknowledgmentsIntroductionPart I: Schooling in Wilhelmine GermanyChapter 1. Schools and Schoolbooks in Wilhelmine GermanyChapter 2. Religious Education in German SchoolsChapter 3. Community: Ordinary Stories and Moral ObligationChapter 4. Homeland, Fatherland, and Distant Lands: Spaces of BelongingChapter 5. Royal Representation of the NationChapter 6. Lessons about War: Sacrifice and Nationhood in Wilhelmine GermanyPart II: Schooling in the Weimar RepublicChapter 7. Schools and Schoolbooks in Weimar GermanyChapter 8. Weimar-Era Religious Instruction: Continuity and ReformChapter 9. Lessons about Community in Weimar Schools: Strong-Armed Men and Dutiful ChildrenChapter 10. Where is the Germans Fatherland? Within and beyond the Weimar BordersChapter 11. Representing the Republic: The Limits of Civic EducationChapter 12. Lessons about War: Mourning and Victimhood in Weimar GermanyPart III: Schooling under the Nazi DictatorshipChapter 13. Schools and Schoolbooks in Nazi GermanyChapter 14. Christian Education in Nazi SchoolsChapter 15. Lessons about Community in the Racial StateChapter 16. Lebensraum in the ClassroomChapter 17. The Hitler Myth for ChildrenChapter 18. Learning to Imagine War, AgainConclusionBibliographyIndex
E-Book / Zugriff nur im Lesesaal